Embolic and thrombotic disorders in the clinical aspects of nervous system vessel disease – prophylaxis and therapy - Palasik, Witold (Przewodnik Lekarza/Guide for GPs, 2005)
Embolic and thrombotic disorders in the clinical aspects of nervous system vessel disease – prophylaxis and therapy. Ischemic cerebral stroke is a serious disease nowadays. The thrombotic etiology is one of its patomechanisms, thus antithrombotic therapy is one of the most efficient in prophylaxis. It should be prescribed cautiously under the INR estimation because of potential dangers. A special subgroup consists of patients with atrial fibrillation. Ablation techniques could be indicated here, but also antithrombotic therapy with INR between 2,0 and 3,0. The safest alternative of antithrombotic agent are heparins, but daily injections are uncomfortable for patients.